Kajian Stok Ikan Lemuru (Sardinella lemuru) yang Didaratkan di Pelabuhan Perikanan Muncar Kabupaten Banyuwangi Provinsi Jawa Timur - Putra, I Nyoman Sastra Adi; Restu, I Wayan; Ekawaty, Rani (Current Trends in Aquatic Science, 2020)
Lemuru fish are pelagic fish that live in shallow marine waters, live in groups, and one of species found at the surface water. The largest population of Lemuru fish in Indonesia is found in the Bali Strait. Based on existing data, the Lemuru condition in Bali Strait waters in particular landed at the Fishery Port of Muncar Beach has decreased. Therefore, a research effort should be made to determine the condition of Lemuru at the Muncar Beach Fishery Port. This study was aimed to determine the distribution of length frequencies, growth pattern, and the stock condition of Lemuru. The study was conducted from May to September 2017. The method used in this study was descriptive research method. Samples of Lemuru are taken randomly and directly from the fishermen's catch, production data, and the number of fishing gear and trip was asked directly from Muncar Fishing Port agency. Results showed the total length frequency distribution of Lemuru fish highest in the 135-137mm long hose from the 120-149 mm interval obtained. The relationship between the length and weight of the Lemuru Fish obtained, follows the equation W=4E-05L2.7677 and negative allometric growth pattern (b<3) which means the length growth more dominant compared to the weight growth. The stock condition of Sardinella lemuru with the TAC value obtained with the amount of 30.940 tons per year and the optimum catches effort or fMsy was 26.802 trips per year. Catched results in 2007 has exceeded from TAC value and catches effort in the last ten years found to be outstrip from the optimum catches effort or fMSY.